Body Language: Affecting Body Satisfaction by Describing the Body in Functionality Terms. (June 2014) - Alleva, Jessica M.; Martijn, Carolien; Jansen, Anita; Nederkoorn, Chantal
With the current studies, we aimed to improve body satisfaction by inducing a functionality-based focus on the body. Objectification theory was used as a guiding framework for this approach. In Study 1, 59 female and 59 male undergraduates and, in Study 2, 118 women between the ages of 30 and 50 years completed a writing assignment to experimentally manipulate their body focus. The writing assignment instructions were to describe what one's body can do (functionality focus) or what one's body looks like (appearance focus); a control writing task was also included. Functionality and appearance satisfaction, as well as global self-esteem, were measured at baseline, on test-day, and at a 1-week follow-up. In Study 1, male undergraduates in the functionality condition experienced an increase in functionality satisfaction from baseline to test-day; female undergraduates in the appearance condition experienced a decrease in functionality satisfaction both from baseline to test-day and from baseline to follow-up. In Study 2, women in the functionality condition experienced an increase in functionality satisfaction from baseline to follow-up. The current studies are the first known to experimentally manipulate the functionality-based approach to the body and to investigate its effects on body image—serving to suggest perceived functionality as a potentially fruitful focus for further research and intervention.